Scheduling Analysis Docking of the Leo Mariner Tug Boat Vessel at PT Using the Critical Path Method - Wagimin Wagimin; Anwar Fattah (Journal La Multiapp, 2026)
So far, ship docking work at the shipyard facility in XYZ has so far not implemented a project scheduling method to optimize performance. Determining the time and scheduling of ship docking work is done based on experience. As a result, there is time and cost inefficiency that impacts low performance, so that the docking and shipping industry is difficult to develop and contribute to the development of the maritime sector. This study aims to optimize the docking schedule of the Leo Mariner Tugboat. The method used is the Critical Path Method (CPM) to determine critical path. Research result shows that the Docking process under existing conditions has 24 activities and 21 paths that require a working time of 100.50 hours. Optimization using CPM produces a critical path with 10 activities and 9 paths that require a working time of 100.50 hours. work for 22.5 hours, or an efficiency of 4.8 % From the base This demonstrates that CPM successfully optimizes ship docking times This finding is beneficial for PT. XYZ in optimizing performance and supporting the development of Indonesia's maritime sector.